The Association Between Allergic Rhinitis and Chronic Suppurative Otitis Media - Simanjutak, Yohana; Zahara, Devira; Sofyan, Ferryan; Ashar, Taufik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tympanic membrane perforation and continuous discharge are hallmarks of chronic suppurative otitis media, a chronic inflammation of the middle ear. Through the malfunction of the Eustachian tube brought on by allergic inflammation, allergic rhinitis may contribute to the development of CSOM. This study aimed to analyze the relationship between allergic rhinitis and CSOM, identify common allergens, and assess the association between eosinophil levels and CSOM. A case-control study was conducted at RSUP H. Adam Malik and RS Murni Teguh Medan involving 72 participants: 36 CSOM patients and 36 healthy controls. Skin prick tests (SPT) and eosinophil counts were used to assess allergic status. Statistical analysis used Chi-square and Fisher’s exact test with significance set at p < 0.05. The results showed a significant association between allergic rhinitis and CSOM (p = 0.001; OR = 6.192). Common allergens found in CSOM patients were D. pteronyssinus (66.7%), D. farinae (63.9%), and cockroach (47.2%), with significant associations (p < 0.05). No significant relationship was found between allergic rhinitis and CSOM sides or type (p > 0.05). Elevated eosinophil levels were more common in the CSOM group but were not statistically significant (p = 0.624). In conclusion, allergic rhinitis is significantly associated with CSOM. Allergen screening is recommended for CSOM patients to improve diagnosis, treatment, and recurrence prevention.